Arbuscular Mycorrhizal Fungi Taxa Show Variable Patterns of Micro-Scale Dispersal in Prairie Restorations - Tipton, Alice G.; Nelsen, Donald; Koziol, Liz; Duell, Eric B.; House, Geoffrey; Wilson, Gail W. T.; Schultz, Peggy A.; Bever, James D. (Frontiers in Microbiology, 2022)
Human land use disturbance is a major contributor to loss of natural plant communities, and this is particularly true in areas used for agriculture, such as Midwestern tallgrass prairies of the United States. Previous work has shown that arbuscular mycorrhizal fungi (AMF) additions can increase native plant survival and success in plant community restorations, but the dispersal of AMF in these systems is poorly understood. Here, we examined dispersal of AMF taxa inoculated into four tallgrass prairie restorations. In each site, we inoculated native plant species with greenhouse cultured native AMF taxa or whole soil collected from nearby unplowed prairie. We monitored AMF dispersal, AMF biomass, plant growth, and plant community composition, at different distances from inoculation. In two sites, we assessed the role of plant hosts in dispersal, by placing known AMF hosts in a “bridge” and “island” pattern on either side of the inoculation points. We found that AMF taxa differ in their dispersal ability, with some taxa spreading to 2-m in the first year and others remaining closer to the inoculation point. We also find evidence that AMF spread altered non-inoculated neighboring plant growth and community composition in certain sites. These results represent the most comprehensive attempt to date to evaluate AMF spread and identifies that AMF spread varies between taxa, is context dependent, and has impacts on neighboring plant communities.